Liplap's wish - London, Jonathan, 1947-; Long, Sylvia (San Francisco : Chronicle Books, 1994)
As he builds a snowbunny, Liplap feels something is missing and wishes his grandmother who recently died was with him.
AD 690
Accelerated Reader AR
Keywords: Grandmothers -- Juvenile fiction; Rabbits -- Juvenile fiction; Death -- Juvenile fiction; Rabbits -- Fiction; Grandmothers -- Fiction; Death -- Fiction